Quia scarabaeus uel cantharus uermis est stercoris. Una glossa erasmiana nel Commentario ad Abacuc di Gerolamo - Mantelli, Sincero (Augustinianum, 2010)
In the main editions of the Commentary by Jerome on the prophet Habakkuk one can read a gloss (« quia scarabaeus uel cantharus uermis est stercoris ») which cannot be found in the manuscript that is usually consulted. The codices show different readings which in most cases quote a corrupt text. Considering that the above-mentioned note does not appear in the pre-Erasmian editions one can draw the conclusion that Erasmus himself corrected the text, adding the meaningful note. To confirm what has been said one can add other corrections, perhaps less significant but which nevertheless can be equally attributed to the hand of the Rotterdam Humanist.